Differentiation syndrome in patients with acute promyelocytic leukemia - Nusiba H. Elamin; Farah Rashid; Muhammad S. Afana; Honar Cherif; Mohamed A. Yassin (Clinical Case Reports, 2023)
Abstract A 48‐year‐old male diagnosed with acute promyelocytic leukemia (APL) started on all‐trans‐retinoic acid and arsenic trioxide, developed typical symptoms of differentiation syndrome, and improved dramatically on steroids. Hence, any APL patient started on chemotherapy, needs to be monitored closely for developing differentiation syndrome and to start steroid upon suspicion.